Chrissy Judy [videorecording (DVD)] - Flaherty, Todd; Fenner, Wyatt; Taranto, Joey; Spencer, Kiyon; Tison, James (Dark Star Pictures, 2023)
Judy's been described as many things: a free spirit, a daydreamer, a boy-crazy hot mess. But this is going to be the summer it all comes together for this ambitious, 30-something drag queen/cater-waiter and his best friend, Chrissy. That is, until Chrissy's priorities suddenly shift, forcing a disillusioned Judy to examine his life and priorities as a queer artist, and rediscover himself in the process. The dark comedy, "Chrissy Judy" explores the universal pain of breaking up with your best friends and questions, "What do you do when your chosen family no longer chooses you?"